Moving Rubber Blade (MRB) for Fouling Control in Anaerobic Ceramic Membrane Bioreactors (AnCMBRs) Treating High-Strength Food Wastewater: Development and Long-Term Application - Young-Jae Lee; Hyung-Soo Kim; Hyunsup Jang; Sung-Gwan Park; Ji-Yeon Kim; Sung-Jae Lee; Youngjin Kim; Moon-Hyun Hwang; Sangyoup Lee (Membranes)
This study investigates membrane fouling control in a submerged anaerobic ceramic membrane bioreactor (AnCMBR) treating high-strength food wastewater (chemical oxygen demand (COD): 10–30 g/L). A hybrid strategy combining mechanical cleaning via a moving rubber blade (MRB) (termed anaerobic ceramic blade MBR (AnCBMBR)) with intermittent salt-assisted backwash (SAB) was tested to manage transmembrane pressure (TMP) and sustain treatment performance. During more than 300 days of field operation, MRB alone maintained stable TMP below 0.15 kgf/cm2 without backwashing, achieving more than 90% COD removal at a very short hydraulic retention time (HRT) of 1–2 days. Introducing intermittent SAB further stabilized operations and enhanced total phosphorus (T-P) removal by facilitating struvite formation through the interaction of MgCl2 and phosphorus in the reactor. The AnCBMBR system demonstrated reliable, long-term fouling control and treatment efficiency, even under high organic loads, proving its viability for small-scale facilities managing concentrated food wastewater. This study advances practical strategies for sustainable anaerobic MBR operation under challenging industrial conditions.